Epigenetic treatment combinations to effectively target cisplatin‐resistant germ cell tumors: past, present, and future considerations. (29th March 2019) - Oing, C.; Skowron, M. A.; Bokemeyer, C.; Nettersheim, D.
Abstract: Background: Type II germ cell tumors represent the most common solid malignancy in men aged 15–45 years. Despite high cure rates of >90% over all stages, 10–15% of advanced patients develop treatment resistance and potentially succumb to their disease. Treatment of refractory germ cell tumors remains unsatisfactory, and new approaches are needed to further improve outcomes. Objectives: With this narrative review, we highlight epigenetic mechanisms related to resistance to standard systemic treatment, which may act as promising targets for novel combined epigenetic treatment approaches. Materials and methods: A comprehensive literature search of PubMed and MEDLINE was conducted to identify original and review articles on resistance mechanisms and/or epigenetic treatment of germ cell tumors in vitro and in vivo . Review articles were hand‐searched to identify additional articles. Results: Distinct epigenetic phenomena have been linked to chemotherapy resistance in germ cell tumors, among which DNA hypermethylation, histone acetylation, and bromodomain proteins appear as promising targets for therapeutic exploitation. Inhibitors of key regulators, for example DNA methyltransferases (e.g. decitabine, guadecitabine), histone deacetylases (e.g. romidepsin), and bromodomain proteins (e.g. JQ1) decreased cell viability, triggered apoptosis, and growth arrest. Additionally, these epigenetic drugs induced differentiation and led to loss of pluripotency and re‐sensitization towards cisplatin in cell lines and animal models. Discussion: Epigenetic treatments hold promise to (i) reduce the treatment burden of and (ii) overcome resistance to standard cisplatin‐based chemotherapy. Combined approaches may enhance activity, while the ideal target and treatment combination of epigenetic drugs, either with another epigenetic agent or conventional cytotoxic agents need to be defined. Conclusion: Epigenetic (combination) treatment for germ cell tumors should be further explored in pre‐clinical and clinical research for its potential to further improve germ cell tumor treatment.